Interesting, isn't it?

Calculus Level 5

0 e 2 t t 2 erf ( t ) d t = A B \large{\displaystyle \int^{\infty}_{0} e^{-2t} t^2 \text{erf} (\sqrt{t} ) \, dt=\frac{\sqrt{A}}{B}}

If the equation above is true for positive integers A A and B B and A A being square free, find the value of A + B A+B .

Note : erf ( x ) \text{erf}(x) is the error function .


The answer is 11.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Pi Han Goh
Nov 1, 2015

Synopsis : Remove the error function by Integration by Parts , then convert the integral into sum of moments of a standard Gaussian distribution.


We first integrate by parts with u = erf ( x ) u = \text{erf}(\sqrt x) , d v = x 2 e 2 x 2 d x dv =x^2 e^{-2x^2} \, dx . So v = 1 4 e 2 x ( 2 x 2 + 2 x + 1 ) v = -\frac14 e^{-2x}(2x^2+2x+1) .

By definition, erf ( x ) = 2 π 0 x e t 2 d t \displaystyle \text{erf}(x) = \frac2{\sqrt \pi} \int_0^x e^{-t^2} \, dt . So by Fundamental Theorem of Calculus , d d x erf ( x ) = 2 π e x 2 \frac{d}{dx} \text{erf}(x) = \frac{2}{\sqrt \pi} e^{-x^2} . And by Differentiation - Chain Rule , d d x erf ( x ) = e x π x \displaystyle \frac d{dx} \text{erf}(\sqrt x) = \frac{e^{-x}}{\sqrt \pi \sqrt x} . Thus,

0 x 2 e 2 x erf ( x ) d x = u d v = u v v d u = [ 2 π 0 x e t 2 d t 1 4 e 2 x ( 2 x 2 + 2 x + 1 ) ] x 0 x 0 + 1 4 π 0 e 2 x ( 2 x 2 + 2 x + 1 ) e x x d x = 1 4 π 0 e 3 x x ( 2 x 2 + 2 x + 1 ) d x , Let y = x d x = 2 y d y = 1 2 π 0 e 3 y 2 ( 2 y 4 + 2 y 2 + 1 ) d y , Let z = 6 y = 1 6 1 2 π 0 e z 2 / 2 ( z 4 18 + z 2 3 + 1 ) d z = 1 2 3 1 2 π 0 ( 1 18 z 4 e z 2 / 2 + 1 3 z 2 e z 2 / 2 + e z 2 / 2 ) d z = 1 4 3 1 2 π ( 1 18 z 4 e z 2 / 2 + 1 3 z 2 e z 2 / 2 + e z 2 / 2 ) d z = 1 4 3 ( 1 18 E ( X 4 ) + 1 3 E ( X 2 ) + E ( X ) ) , where X denote the Gaussian distribution = 1 4 3 ( 1 18 3 ! ! + 1 3 1 ! ! + 1 ) = 3 8 \begin{aligned} & \int_0^\infty & x^2 e^{-2x} \text{erf}(\sqrt x) \, dx \\ &=& \int u \, dv \\ &=& uv - \int v \, du \\ &=& \cancelto{0}{\left[ \frac2{\sqrt \pi} \int_0^x e^{-t^2} \, dt \cdot -\frac14 e^{-2x}(2x^2 + 2x + 1) \right]_{x\to0}^{x\to\infty}} + \frac1{4\sqrt \pi} \int_0^\infty e^{-2x}(2x^2 + 2x + 1) \frac{e^{-x}}{ \sqrt x} \, dx \\ &=& \frac1{4\sqrt \pi} \int_0^\infty \frac{e^{-3x}}{\sqrt x} (2x^2 + 2x + 1) \, dx \quad, \quad \color{#69047E}{\text{Let } y = \sqrt{x} \Rightarrow dx = 2y \, dy} \\ &=& \frac1{2\sqrt \pi} \int_0^\infty e^{-3y^2} (2y^4 + 2y^2 + 1) \, dy \quad, \quad \color{#69047E}{\text{Let } z= \sqrt6 y} \\ &=& \frac1{\sqrt6} \frac1{2\sqrt \pi} \int_0^\infty e^{-z^2/2} \left( \frac{z^4}{18} + \frac{z^2}3 + 1 \right) \, dz \\ &=& \frac1{2\sqrt3} \frac1{\sqrt{2\pi}} \int_0^\infty \left( \frac1{18} z^4 e^{-z^2/2} + \frac13 z^2 e^{-z^2/2} + e^{-z^2 /2} \right) \, dz \\ &=& \frac1{4\sqrt3} \frac1{\sqrt{2\pi}} \int_{-\infty}^\infty \left( \frac1{18} z^4 e^{-z^2/2} + \frac13 z^2 e^{-z^2/2} + e^{-z^2 /2} \right) \, dz \\ &=& \frac1{4\sqrt3} \cdot \left ( \frac1{18} E(X^4) + \frac13 E(X^2) + E(X) \right) \quad, \quad \color{#69047E}{\text{where }X\text{ denote the Gaussian distribution } } \\ &=& \frac1{4\sqrt3} \cdot \left( \frac1{18} \cdot 3!! + \frac13 \cdot 1!! + 1 \right) \\ &=& \boxed{ \dfrac{\sqrt 3}8 } \\ \end{aligned}


Note : The m th m^\text{th} moment of a Gaussian distribution can be found here .

Whoa!! Nice , thanks for the link, BTW did u like the problem.

Tanishq Varshney - 5 years, 7 months ago

Log in to reply

YES OF COURSE

Pi Han Goh - 5 years, 7 months ago
Kartik Sharma
Nov 1, 2015

I know of 2 ways, out of which I will give the solution of one(which is easier and better) and an idea of the other.

erf ( t ) = 2 π 0 t e m 2 d m \displaystyle \text{erf}(\sqrt{t}) = \frac{2}{\sqrt{\pi}} \int_{0}^{\sqrt{t}}{e^{-m^2}\, \mathrm{d}m}

Now we consider our integral as -

I ( n ) = 0 e 2 t t 2 erf ( n t ) d t \displaystyle I(n) = \int_{0}^{\infty}{e^{-2t} t^2 \text{erf}(n \sqrt{t})\, \mathrm{d}t}

and thus we need to find I ( 1 ) I(1)

We would use Leibnitz integral rule

d d x ( a ( x ) b ( x ) f ( x , t ) d t ) = f ( x , b ( x ) ) b ( x ) f ( x , a ( x ) ) a ( x ) + a ( x ) b ( x ) x f ( x , t ) d t \displaystyle \frac{\mathrm{d}}{\mathrm{d}x} \left (\int_{a(x)}^{b(x)}f(x,t)\,\mathrm{d}t \right) = f(x,b(x))\cdot b'(x) - f(x,a(x))\cdot a'(x) + \int_{a(x)}^{b(x)} \frac{\partial}{\partial x}f(x,t)\; \mathrm{d}t

and get that d d n ( erf ( n t ) ) = 2 t e n 2 t π \displaystyle \frac{\mathrm{d}}{\mathrm{d}n}(\text{erf}(n \sqrt{t})) = \frac{2\sqrt{t} e^{-n^2 t}}{\sqrt{\pi}}

Hence,

I ( n ) = 0 e 2 t t 2 2 t e n 2 t π d t \displaystyle I'(n) = \int_{0}^{\infty}{e^{-2t} t^2 \frac{2\sqrt{t} e^{-n^2 t}}{\sqrt{\pi}}\, \mathrm{d}t}

This is a simple Laplace transform,

I ( n ) = 2 Γ ( 7 2 ) π ( n 2 + 2 ) 7 / 2 \displaystyle I'(n) = \frac{2 \Gamma\left(\frac{7}{2}\right)}{\sqrt{\pi} (n^2+2)^{7/2}}

0 1 I ( n ) d n = 0 1 2 Γ ( 7 2 ) π ( n 2 + 2 ) 7 / 2 d n \displaystyle \int_{0}^{1}{I'(n) \, \mathrm{d}n} = \int_{0}^{1}{\frac{2 \Gamma\left(\frac{7}{2}\right)}{\sqrt{\pi} (n^2+2)^{7/2}} \, \mathrm{d}n}

I will not go into the computation of this integral since it is kinda trivial one.

I ( 1 ) I ( 0 ) = 2 π Γ ( 7 2 ) 10 3 \displaystyle I(1) - I(0) = \frac{2}{\sqrt{\pi}} \frac{\Gamma\left(\frac{7}{2}\right)}{10 \sqrt{3}}

I ( 1 ) = 2 π 15 π 8 10 3 \displaystyle I(1) = \frac{2}{\sqrt{\pi}} \frac{\frac{15\sqrt{\pi}}{8}}{10 \sqrt{3}}

= 3 8 \displaystyle = \boxed{\frac{\sqrt{3}}{8}}

The other method uses the summation definition of error function and it can take quite a lot of energy even with hypergeometric(if not yours, your computer anyway).

@Tanishq Varshney You have any other methods?

Kartik Sharma - 5 years, 7 months ago

Log in to reply

Nope, but a slightly different method ( you can say) .I found Laplace transformation of erf( sqrt(t)) and then some properties.

Tanishq Varshney - 5 years, 7 months ago

Log in to reply

Can you post your solution? I'm typing out a simple IBP solution as we speak.

Pi Han Goh - 5 years, 7 months ago

You provided a brilliant solution!! Thanx.

Tanishq Varshney - 5 years, 7 months ago

This is a simple Laplace transform

I'm not that familiar with Laplace. How do you know that it's in a "Laplace form"? And how do you convert it to I ( n ) = 2 Γ ( 7 2 ) π ( n 2 + 2 ) 7 / 2 \displaystyle I'(n) = \frac{2 \Gamma\left(\frac{7}{2}\right)}{\sqrt{\pi} (n^2+2)^{7/2}} ?

Pi Han Goh - 5 years, 7 months ago

Log in to reply

Well, that's quite easy. Isn't it? That is simply 2 π 0 t 7 / 2 1 e ( n 2 + 2 ) t \displaystyle \frac{2}{\sqrt{\pi}}\int_0^\infty {t^{7/2 -1} e^{-(n^2+2)t}} . From now, you can use u-substitution and Gamma function or use the result of the Laplace transform of t n t^n i.e. 0 t n e s t d t = Γ ( n + 1 ) s n + 1 \displaystyle \int_{0}^{\infty}{t^n e^{-st} \, \mathrm{d}t} = \frac{\Gamma(n+1)}{s^{n+1}} Yeah, that it obvious from the u-substituti... but we want a formula for many such functions. So, we make a table of functions f ( x ) f(x) along with their Laplace transform, 0 f ( x ) e s x d x \int_{0}^{\infty}{f(x) e^{-sx}\, \mathrm{d}x} . You just need to peep into the table and put in the value but false, it isn't for destroying the beauty of integration, it is for solving differential eqns(as you know) and we should try not to copy much of these. (I committed a mistake).

Kartik Sharma - 5 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...